Keeping Family in an Age of Long Distance Trade, Imperial Expansion, and Exile, 1550-1850 - Dalton, Heather (Book collections on Project MUSE., 2020)
Keeping Family in an Age of Long Distance Trade, Imperial Expansion and Exile, 1550-1850 brings together eleven original essays by an international group of scholars, each investigating how family, or the idea of family, was maintained or reinvented when husbands, wives, children, apprentices, servants or slaves separated, or faced separation, from their household. The result is a fresh and geographically wide-ranging discussion about the nature of family and its intersection with travel over a three hundred year period during which roles and relationships, within and between households, were increasingly affected by trade, settlement, and empire building. The imperial project may have influenced different regions in different ways at different times yet, as this collection reveals, families, especially those transcending national ties and traditional boundaries were central to its progress. Together, these essays bring new understandings of the foundations of our interconnected world and of the people who contributed to it.